1998
DOI: 10.1177/000456329803500603
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Bone Alkaline Phosphatase in Osteoporosis

Abstract: SUMMARY. We have evaluated two commercial assays for serum bone specific alkaline phosphatase (bALP) as a marker of bone turnover in a group of 35 postmenopausal women with osteoporosis during their first year of treatment with the anti-resorptive drug, alendronate. The immunoradiometric assay (bALP-I) measured protein mass, whereas the immunocapture assay (bALP-E) measured activity.Before treatment, bALP values with both methods were within the postmenopausal reference ranges. Treatment with alendronate produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…The values for serum calcium, phosphate, total alkaline phosphatase and PTH did not change signi®cantly during the study. Bone marker changes in patients pretreated with etidronate and those not pretreated from this cohort of patients have been reported previously [7,8]. The patients showed a signi®cant decline in bone turnover at 6 months after alendronate treatment, and there was no signi®cant difference in the changes between the etidronatepretreated patients and those not pretreated.…”
Section: Resultssupporting
confidence: 69%
“…The values for serum calcium, phosphate, total alkaline phosphatase and PTH did not change signi®cantly during the study. Bone marker changes in patients pretreated with etidronate and those not pretreated from this cohort of patients have been reported previously [7,8]. The patients showed a signi®cant decline in bone turnover at 6 months after alendronate treatment, and there was no signi®cant difference in the changes between the etidronatepretreated patients and those not pretreated.…”
Section: Resultssupporting
confidence: 69%
“…Recent study has also shown that the activity of serum total ALP >129 U/L is used as an indicator for osteoporosis in men [16]. Moreover, the decrease of total ALP has been demonstrated with the treatment with alendronate from 79.7 U/L to 64.8 U/L [17]. The results indicate that total ALP can be used as an indicator to reflect the efficiency of drug treatment for osteoporosis.…”
Section: Bone Formation Biomarkersmentioning
confidence: 98%
“… 17 B-ALP is more specific for bone and, therefore, more sensitive in detecting the small changes in bone formation seen in osteoporosis. 17 18 OC is considered a specific biomarker of osteoblast function for the evaluation of bone formation rate in osteoporosis. 5 17 The concentration of P1NP and P1CP in serum reflects bone formation rate, 17 as they are produced during conversion of procollagen type 1 to collagen type 1.…”
Section: Bone Turnover Biomarkersmentioning
confidence: 99%